An Experimental Study of Information Revelation Policies in Sequential Auctions - Cason, Timothy N.; Kannan, Karthik N.; Siebert, Ralph (Management Science, 2011)
Theoretical models of information asymmetry have identified a trade-off between the desire to learn and the desire to prevent an opponent from learning private information. This paper reports a laboratory experiment that investigates if actual bidders account for this trade-off, using a sequential procurement auction with private cost information and varying information revelation policies. Specifically, the Complete Information Revelation Policy, where all submitted bids are revealed between auctions, is compared to the Incomplete Information Revelation Policy, where only the winning bid is revealed. The experimental results are largely consistent with the theoretical predictions. For example, bidders pool with other types to prevent an opponent from learning significantly more often under a Complete Information Revelation Policy. Also as predicted, the procurer pays less when employing an Incomplete Information Revelation Policy only when the market is highly competitive. Bids are usually more aggressive than the risk-neutral quantitative prediction, which is broadly consistent with risk aversion. This paper was accepted by Teck Ho, decision analysis.